EKSTRAKSI ASAM LEMAK BEBAS DARI MINYAK NABATI DENGAN METANOL KAJIAN PERPINDAHAN MASSA - Wahyuningsih Wahyuningsih; Moh Endy Yulianto (Vocational School Diponegoro University, 2012)
Wahyuningsih, Moh Endy Yulianto, in this paper explain that extraction of free fatty acids from vegetable oils with methanol performed in batch stirred tank, in a variety of conditions. Variables experiments in liquid-liquid extraction including temperature, solvent ratio and rotational speed stirrer. This study aims to develop a correlation coefficient of mass transfer in extraction of free fatty acids from vegetable oils methanol. Rresearch was conducted in two phases. Was the first stage liquid-liquid extraction experiments in laboratory. Second step is the development of an empirical correlation for the mass transfer coefficients in the form of numbers not berdemensi results showed that the greater the temperature, turn the mixer speed and solvent-feed ratio of the mass transfer koffisien gained greater. Mass transfer coefficient expressed in Sherwood number and correlated against the Reynolds number, Schmitd, (dP / dT) and (L / S), the results obtained: Sh = 4,669 x 10-5 Re 0,462 Sc0,5 (dP/dT)0,308 (L/S)0,187 If used to calculate the mass transfer coefficients, have an average error of 8.79% for the regression line. This equation was developed in the Re number range 3169 to 11 750; numbers Sc 6321 to 9896, (dp / dT) from 0.0007 to 0.0013 and (L / S) of 0.333 to 1. Keywords: nabati oil extraction